Nitric Oxide Cooperates With Auxin to Mitigate the Alterations in the Root System Caused by Cadmium and Arsenic - Piacentini, Diego; Della Rovere, Federica; Sofo, Adriano; Fattorini, Laura; Falasca, Giuseppina; Altamura, Maria Maddalena (Frontiers in Plant Science, 2020)
Oryza sativa L. is a worldwide food-crop frequently growing in cadmium (Cd)/arsenic (As) polluted soils, with its root-system as the first target of the pollutants. Root-system development involves the establishment of optimal indole-3-acetic acid (IAA) levels, also requiring the conversion of the IAA natural precursor indole-3-butyric acid (IBA) into IAA, causing nitric oxide (NO) formation. Nitric oxide is a stress-signalling molecule. In rice, a negative interaction of Cd or As with endogenous auxin has been demonstrated, as some NO protective effects. However, a synergism between the natural auxins (IAA and/or IBA) and NO was not yet determined and might be important for ameliorating rice metal(oid)-tolerance. With this aim, the stress caused by Cd/As toxicity in the root cells, and the possible recovery by either NO or auxins (IAA/IBA), was evaluated after Cd or As (arsenate) exposure, combined or not with the NO-donor compound sodium-nitroprusside (SNP). Root fresh weight, membrane electrolyte leakage, and H2O2 production were also measured. Moreover, endogenous IAA/IBA contents, transcription-levels of OsYUCCA1 and OsASA2 IAA-biosynthetic-genes, and expression of the IAA-influx-carrier OsAUX1 and the IAA-responsive DR5::GUS construct were analysed, and NO-epifluorescence levels measured. Results showed that membrane injury by enhanced electrolyte leakage occurred under both pollutants, and was reduced by the treatment with SNP only in Cd-presence. By contrast, no membrane injury was caused neither by exogenous NO nor IAA or IBA. Cd- and As-toxicity also resulted into a decreased root fresh weight, mitigated by the combination of each pollutant with either IAA or IBA. Cd and As decreased the endogenous NO-content, increased H2O2 formation, and altered auxin biosynthesis, levels and distribution in both adventitious (ARs) and mainly lateral roots (LRs). The SNP-formed NO counteracted the pollutants’ effects on auxin distribution/levels, reduced H2O2 formation in Cd-presence, and enhanced AUX1-expression, mainly in As-presence. Each exogenous auxin, but mainly IBA, combined with Cd or As, mitigated the pollutants’ effects by increasing LR-production, and by increasing NO-content, in the case of Cd. Altogether, results demonstrate that NO and auxin(s) work together in the rice root system to counteract the specific toxic-effects of each pollutant.